1996
DOI: 10.1046/j.1365-2125.1996.36916.x
|View full text |Cite
|
Sign up to set email alerts
|

Excursions in biomedical mass spectrometry

Abstract: 1Mass spectrometry (MS) has played a vital role in the research of the department of clinical pharmacology for over 25 years. 2MS has been used for trace analysis of endogenous compounds and xenobiotics in plasma and urine, and also for a wide range of structural studies. 3Examples of current applications are reported, including data from gas chromatography‐mass spectrometry (GC‐MS) assays for mevalonic acid, the identification of an antibiotic produced by Pseudomonas aeruginosa which is active against Heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Previous analysis of gliotoxin has suggested that the molecule fragments when mass spectrometry is used as a means of detection (Taylor et al, 1996), thus it is likely that gliotoxin has been cleaved or degraded from BSA conjugates resulting in the appearance of an incorrect conjugate m/z ratio by mass spectrometry. Thus, we believe the estimate of 15 mol gliotoxin/mol BSA by SDS-PAGE is a more reliable estimate of hapten loading.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analysis of gliotoxin has suggested that the molecule fragments when mass spectrometry is used as a means of detection (Taylor et al, 1996), thus it is likely that gliotoxin has been cleaved or degraded from BSA conjugates resulting in the appearance of an incorrect conjugate m/z ratio by mass spectrometry. Thus, we believe the estimate of 15 mol gliotoxin/mol BSA by SDS-PAGE is a more reliable estimate of hapten loading.…”
Section: Discussionmentioning
confidence: 99%